Pengembangan Bahan Ajar Literasi dan numerikal berbasis Masalah dan Proyek untuk Anak Usia 5-6 Tahun - sutama, i wayan (Jurnal Graha Pengabdian, 2023)
Abstract— The purpose of this training is to increase the knowledge and skills of teachers in developing problem- and project-based literacy and numerical teaching materials for children aged 5-6 years. This is significant to be implemented, because through the independent curriculum children are directed to have and master literacy and numeracy skills, in addition to having religious values and character and identity. Meanwhile, so far learning is more directed at low-level learning outcomes and tends to be linear and routine. Children tend to only follow the directions and examples of the teacher and get a partial learning experience. The methods used include material deepening activities, workshops, peer and expert reviews, field trials, finalizing games and uploading good learning practices on social media. The results of the training show that the level of participation, activity and ability to develop problem-based and project-based teaching materials is very high. In addition, almost all participants are interested and challenged by this program, so it needs to be followed up with intensive assistance. Another impact of these activities are that children become more active, creative and productive in playing, and on  very high literacy and numeracy mastery.